THE ROLE OF ACHIEVEMENT MOTIVATION MEDIATION IN THE INFLUENCE OF EMPLOYEE MUTATION AND INTERNAL COMMUNICATION ON EMPLOYEE PERFORMANCE (A STUDY AT KPP PRATAMA SERANG BARAT) - Hidayat, Taufiq; Prahiawan, Wawan; Kambara, Roni (Ridwan Institute, 2024)
This study aims to measure the influence of employee mutation and internal communication on employee performance with achievement motivation as a mediating variable. This study was conducted at the West Serang Pratama Tax Service Office using a questionnaire as the main data collection tool, which included respondent profiles and questions related to the variables studied. The results of this research are expected to contribute to knowledge in human resource management, especially related to employee mutation, internal communication, achievement motivation and its effect on employee performances and can be used as the reference for further research and development. The mediation test proves that achievement motivation can mediate internal communication relationships on employees' performance.